PANEL COINTEGRATION ANALYSIS IN DETERMINING RELATIONSHIP OF AGRICULTURAL COMMODITY AND OIL FUEL PRICE IN INDONESIA - Marizsa Herlina (Indonesian Journal of Statistics and Applications, 2020)
This paper contributes to explain the relationship between oil fuel prices, oil price, the exchange rates, and agricultural commodity prices in Indonesia by using panel cointegration. Thus, this paper studied the short- and long-run relationships between oil fuel prices, oil prices, exchange rates, and agricultural commodity prices using the panel cointegration and causality analysis on five main agricultural commodities in Indonesia (i.e. rice, beef, palm oil, red chili, and sugar). The study was conducted using weekly agricultural, oil fuel, oil prices, and exchange rates from October 2014 until May 2016. The results showed that the oil fuel prices and the exchange rate had a long-run impact on agricultural commodity prices. The direction of the causality had also been determined. The oil fuel prices, oil prices, and exchange rate altogether had a unidirectional Granger causality to all of the agricultural commodity prices except beef and palm oil prices in the long-run.